(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
Diversity at molecular level among thirty rice genotypes, selected based on earliness and morphometric diversity was evaluated through five SSR markers associated with days to heading. Three primers viz., RM147, RM167 and RM215 showed polymorphism for growth duration related traits. A total of 17 alleles were detected among the 30 rice genotypes with an average of 5.66 alleles per locus. Polymorphism Information Content (PIC) ranged from 0.356 to 0.798 with an average of 0.543. A dendrogram based on total microsatellite polymorphism grouped 30 genotypes into four major clusters at 0.39 similarity coefficient differentiating early maturing genotypes from others. This information about the genetic diversity will be very useful for proper identification and selection of appropriate parents for future breeding programs, including gene mapping. The results also showed that microsatellite markers associated to genes or QTLs controlling growth duration properties are suitable tools for marker assisted selection (MAS) to select rice lines with short growth duration. DOI: http://dx.doi.org/10.3329/ralf.v1i1.22354 Res. Agric., Livest. Fish.1(1): 37-46, Dec 2014